Born criminal : Matilda Joslyn Gage, radical suffragist - Carpenter, Angelica Shirley (South Dakota Historical Society Press, 2018)
Radical, feminist, writer, suffragist Matilda Joslyn Gage changed the course of history. She fought for equal rights not dependent on sex, race, class, or creed. Yet her name has faded into obscurity. She is forgotten when her comrades, Susan B. Anthony and Elizabeth Cady Stanton, are celebrated. To explain, Angelica Shirley Carpenter explores Gage's life, including her rise and fall within the movement she helped build. --amazon.com.